(untitled) (Damascus University Journal for legal sciences, 2026)
The issues of privacy and gender have always been classified as issues of high importance in society, and with the widespread use of technology and the Internet in our current era, the concept of privacy has evolved into the digital form represented by personal data with the sensitive information contained in this data and accurate details about its owner. However, this development of the concept of privacy carried with it a negative impact, embodied in the ease of violating this data as a result of the lack of the necessary technical protection, and the consequences of this breach affecting a number of rights related to the right to privacy of women. Therefore, the duty to provide an international legal framework that protects women’s privacy with its digital concept and tools represented by the Internet, social media and digital applications is an urgent necessity.